HUBUNGAN KONFLIK ANTARWARGA DENGAN KEAMANAN KEMANUSIAAN DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (STUDI TAWURAN WARGA DI KECAMATAN JOHAR BARU JAKARTA PUSAT 2010-201) - Munawar _ (Universitas Gadjah Mada, 2013)
This paper explained the residents’ conflicts in Jakarta. The qualitative and quantitative data showed the significant relations of conflict, security and regional resilience. Therefore to eliminated the conflicts, the taken strategy was creating employment, enhancing education level, enhancing the community life and enhancing the social control function role which embodied in security forces assertiveness in conflict resolution including intelligence forces’ early preventing.Keywords: Residents’ Conflict, Human Security, and Regional Resilience.